Engineering mechanics dynamics - Russel Charles Hibbeler (Prentice-Hall, 1995)
This book provides a clear and thorough presentation of the theory and applications of engineering mechanics. The problem sets have been greatly expanded. Often, several problem statements refer to the same drawing. Numerous problems in the book depict realistic situations encountered engineering practice. Some problems may be solved using a numerical procedure executed on either a desktop computer or a programmable pocket calculator. The answers to all but every fourth problem are listed in the back of the book. A problem without a reported answer, an asterisk (*) is placed before the problem number